PENINGKATAN PRODUKTIVITAS PADI MENGGUNAKAN PUPUK HAYATI DI LAHAN PASANG SURUT TIPE B - Andin Muhammad Abduh; Masganti Masganti; Nukhak Nufita Sari (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Rice productivity in tidal land is still low due to the chemical, physical, and biological properties of the soil. The research was carried out in January-May 2020 on tidal land type B, Maluka Baulin Village, Kurau District, Tanah Laut Regency, South Kalimantan Province. The aim of the study was to determine the best combination of fertilizer doses in increasing rice productivity. The treatments included (A) farmer treatment (200 kg urea + 150 kg phonska + 500 kg dolomite)/ha; (B) farmer treatment + liquid fertilizer (6 liters/ha); (C) (200 kg urea + 300 kg phonska + 1,000 kg dolomite + 100 kg KCl + 100 kg SP-36 + 500 kg crumb fertilizer + 6 liters of liquid fertilizer)/ha; and (D) (200 kg urea + 300 kg phonska + 1,000 kg dolomite + 100 kg KCl + 100 kg SP-36 + 250 kg crumb fertilizer + 3 liters of liquid fertilizer)/ha. The treatment used a nested design with four replications. M400 rice seeds were planted with the Jarwo 4:1 system. Observations were made on the chemical properties of the soil before planting, growth and productivity of rice. The results showed that all parameters, except the number of tillers aged 60 DAP and before harvest were strongly influenced by the treatment. The highest productivity resulted from treatment D.